2017
DOI: 10.1248/bpb.b17-00212
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Transcription Factor Sp1 Suppresses Malignant Properties of A549 Human Lung Cancer Cell Line with Decreased β4-Galactosylation of Highly Branched <i>N</i>-Glycans

Abstract: Dramatic changes in the glycan structures of cell surface proteins have been observed upon malignant transformation of cells as induced by the altered expression levels of glycosyltransferases. Such changes are closely associated with the malignant properties of cancer cells. Transcription factor Sp1 regulates the gene expression of various molecules including glycosyltransferases. Herein, we investigated whether or not Sp1-downregulation affects to N-glycosylation of glycoproteins and malignant properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The results of luciferase assay were analyzed with the analysis of variance followed by the Bonferroni correction for multiple comparisons. The results of quantitative real-time RT-PCR analysis were analyzed by Student's t-test [10,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of luciferase assay were analyzed with the analysis of variance followed by the Bonferroni correction for multiple comparisons. The results of quantitative real-time RT-PCR analysis were analyzed by Student's t-test [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter activities of the sensor cells were determined by luciferase assay as described previously [10,14,17].…”
Section: Luciferase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…β4GalT family consists of seven members with different substrate specificity and tissue distribution. 6) Among β4GalT family, the transcription of the human β4GalT1, β4GalT3, β4GalT4, and β4GalT5 genes was reported to be regulated by Sp1. [7][8][9][10] Recently, we demonstrated that downregulation of Sp1 suppresses the malignant potentials of A549 human lung cancer cell line with the reduced β4-galactosylation of highly branched N-glycans on cell surface glycoproteins, which is resulted in the decreased expression of the β4GalT1 gene.…”
Section: Introductionmentioning
confidence: 99%